Oral History Program Interview Earl Butler - Butler, Earl
Born in Missouri in 1929, Butler came with his family to Lindsay, California in October of 1937. He considers his and other migrants' experiences like facing discrimination for being a migrant at work and in school, organizing in late 1930s and early 1940s, growers cheating migrants out of pay, The Grapes of Wrath depicting aspects of the Dust Bowl migrants' plight, relief received, and differences between "Okies" and Californians.